SOME ISSUES OF BUSINESS TERMS BORROWED FROM ENGLISH - Hasanov Elyorjon Odiljonovich (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
: The article is devoted to the study of the problem of business terms in translation process from English into Uzbek. Moreover, it discusses some features of terms and terminology in English and Uzbek languages